Changes in humeral retrotorsion and the development of little league shoulder: A case study. (November 2018) - Greenberg, Elliot M.; Turner, Christian; Huse, Casey; Ganley, Theodore J.; McClure, Philip; Lawrence, J. Todd
Abstract: Objective: To present the case of a 15 year-old baseball player with Little League Shoulder (LLS) and describe how developmental changes in the angle of humeral retrotorsion (HRT) may contribute to the underlying pathology of this condition. Design: Case report. Setting: Two years earlier, the patient had participated in a healthy player screening program at which time measurements of height, weight, shoulder motion, and HRT were obtained. These same measures were obtained during the initial evaluation after injury. Between measurements, the patient grew more than 12 cm in height and demonstrated a large shift in proximal humeral torsional alignment with a change of 13° and 19° of HRT in the dominant and non-dominant sides respectively. Participant: 15 year-old male (1.88 m, 79.8 kg), right hand dominant baseball pitcher and 3rd baseman diagnosed with right LLS. Conclusion: The pathoanatomical factors contributing to LLS are not well understood. The degree of HRT is a developmental characteristic that changes over the course of physiological maturation. The large changes in HRT seen in this case, may implicate rapid changes in HRT angle create a window of increased susceptibility to physeal damage, and contribute to the development of LLS.